PENGOLAHAN TEPUNG DAN BUBUR INSTAN DARI GANYONG (CANNA EDULIS KERR.) MELALUI PENGERINGAN DRUM - Rodiahwati, Wawat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Edible canna (Canna edulis Kerr.) is one of local tubers that has high content of starch so it can be used for food diversification. Processing technology that has been applied so far is to make transparent starch noodle (Roisah, 2009) and canna starch (Ciptadi et al. 1980). The aim of this research is to explore the process characteristics and quality of drum dried instant canna powder that can be rehydrated into edible canna porridge. Dried edible canna had been successfully made from edible canna slurry developed from cooked mashed red edible canna corm from farmers in Bogor district and then dried using double drum dryer. Preliminary research was applied to determine the best cooking time and RPM of the double drum dryer. Fifty minutes and three RPM were determined as the best in instant canna powder brightness so it were used in the following research phases. Two treatments were applied, 1) feed slurry composition at three levels, 1:2, 1:3, and 1:4 (ratio cooked mash edible canna to water) and 2) steam pressure at also three levels, 300 kPa, 400 kPa, and 500 kPa.The results indicated that dried canna powder produced at 500 kPa steam pressure combined with 1:4 feed slurry composition had the best moisture content that was 5.07% and it had the best brightness, 83.25. The organoleptic test, however, suggested that taste, aroma, and color of edible canna porridge rehydrated from dried instant edible canna powder was favoured for the combination treatment of steam pressure 500 kPa and 1:2 feed slurry concentration. Treatment of steam pressure 500 kPa and 1:3 feed slurry concentration had the highest viscosity that was 10 200 cp. The treatment of steam pressure and feed slurry composition had significant effect on moisture content and the organoleptic test. While viscosity and brightness were not affected significantly.